Innovative Strategy Implementation of Teaching Materials Assisted Based Culture and Character Nation To Improve Student Learning Outcomes - Kurniah, Nina (Universitas Negeri Semarang, 2014)
This study aims to improve student learning outcomesÃ‚Â in Prodi APGPAUD FKIP Bengkulu University through the implementation of innovative strategies namely Contextual Teaching and Learning assistedÃ‚Â teaching materials based on theÃ‚Â culture and character nation. To achieve these objectives done Classroom Action ResearchÃ‚Â by using a model of Kemmis through four stages of planning, implementation of action, observation and reflection. The subjects were students of PG Paud force in 2013, amounting to 36 people. Data collection techniques used were observation, interviews, and documentation. Research data collected quantitative and qualitative. Quantitative data were analyzed using the statistical t-test while the qualitative data were analyzed an inductively model of